An Ultraviolet Fluorophore with Narrowed Emission via Coplanar Molecular Strategy. Issue 48 (26th October 2022) - He, Xin; Lou, Jingli; Li, Baoxi; Wang, Han; Peng, Xiaoluo; Li, Ganggang; Liu, Lu; Huang, Yu; Zheng, Nan; Xing, Longjiang; Huo, Yanping; Yang, Dezhi; et al.
Abstract: Narrowband emitting fluorophores exhibit immense potentials for organic light‐emitting diodes (OLEDs) with high color purity. However, it's still hard to simultaneously realize short‐wavelength ultraviolet (UV) or near ultraviolet emission (NUV) while maintaining a narrowed full width at half maximum (FWHM) value, and rare work focus on such challenging pursuit. Herein, an ingenious synthetic method was devised to achieve emitters with coplanar structure. 11‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)indolo[3, 2, 1‐ jk ]carbazole (ICZ‐TAZ) was designed to realize narrowed UV emission both in photoluminescence (PL) and electroluminescence (EL) which benefited from the suppression of vibronic coupling. UV/NUV OLEDs based on ICZ‐TAZ achieve external quantum efficiency (EQE) maximums of 3.26 % peaks @ 388 nm and 4.02 % peaks @ 406 nm with small FWHM of 32 nm and 46 nm, respectively, corresponding with reduced efficiency roll‐off at luminance of 100 cd m −2 . Abstract : A coplanar strategy using indolo[3, 2, 1‐ jk ]carbazole (ICZ) simultaneously achieves narrowed emission and ultraviolet (UV) emission in fluorescent organic light‐emitting diodes (OLEDs), and a synthetic shortcut is carried out to efficiently obtain the target coplanar ICZ derivatives. 11‐(4, 6‐diphenyl‐1, 3, 5‐triazin‐2‐yl)indolo[3, 2, 1‐ jk ]carbazole (ICZ‐TAZ) shows UV emission with peaks below 400 nm and narrowed full width at half maximum (FWHM) both in photoluminescence and electroluminescence, achieving best results among fluorescent UV‐OLEDs.